2014
DOI: 10.1590/1807-55092014000400553
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and lipid profile in young women: the role of anthropometric measurement

Abstract: ) and %BF (≥ 30%), respectively. BMI and % BF were positively correlated with blood pressure (systolic and diastolic), and highly signifi cant in the obese group by %BF. Moreover, BMI and % BF were signifi cantly correlated with all lipids and lipoprotein fractions VLDL-c and triglyceride, respectively. These results suggest that %BF is a good indicator of "occult obesity" in subjects with normal body mass index. The associated use of BMI and %BF to better evaluate obesity may improve the study of blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Kim, Yoo, Jeon, Kim, Choi, Park, & Lee [13] investigated the relationship concerning WC and WSR with metabolic syndrome in females and found that WSR exhibited a stronger correlation with metabolic syndrome than WC. In a study by Rubira, Rubira, Rubira, Lima, Franco, and Consolim-Colombo [14], BMI and BF% were positively linked with blood pressure, BF% was greatly important in the overweight group. While some research have studied the relationship with various obesity indices and metabolic risk factors, including BF%, BMI, WC, and WHR, there is still no clear consensus on which index is the most strongly associated with blood pressure and blood lipids.…”
Section: Introductionmentioning
confidence: 92%
“…Kim, Yoo, Jeon, Kim, Choi, Park, & Lee [13] investigated the relationship concerning WC and WSR with metabolic syndrome in females and found that WSR exhibited a stronger correlation with metabolic syndrome than WC. In a study by Rubira, Rubira, Rubira, Lima, Franco, and Consolim-Colombo [14], BMI and BF% were positively linked with blood pressure, BF% was greatly important in the overweight group. While some research have studied the relationship with various obesity indices and metabolic risk factors, including BF%, BMI, WC, and WHR, there is still no clear consensus on which index is the most strongly associated with blood pressure and blood lipids.…”
Section: Introductionmentioning
confidence: 92%
“…To date, few studies have examined whether lipid levels are associated with the risk of hypertension in young adults [11][12][13]. Data on the relationship between hypertension and lipid profile among the young Polish population are rare in the literature and inconclusive.…”
Section: Introductionmentioning
confidence: 99%